Analysis of fatty acids in Ghee and olive oil and their probable causal effect in lipoid pneumonia (Faculty of Medicine Universitas Indonesia, 2010)
Aim: To analyze and identify the fatty acids found in homemade ghee and in olive oil and compare those to fatty acids found in bronchoalevolar lavage of children with lipoid pneumonia. Methods: The fatty acids found in homemade fat